Application of stoma powder, skin protective film and hydrocolloid dressing and one-piece ostomy pouch in ICU patients with incontinence-associated dermatitis (护肤粉、皮肤保护膜、水胶体敷料联合一体式造口袋在ICU失禁性皮炎患者的应用) - ZHU Congmei (朱丛梅) (中西医结合护理)
Objective To investigate the effect of combination use of stoma powder, skin protective film and hydrocolloid dressing and one-piece ostomy pouch in ICU patients with incontinence-associated dermatitis (IAD). Methods Totally 40 ICU patients with IAD were divided into control group and observation group according to the order of hospitalization. Patients in the control group were given routine nursing management, while patients in the observation group were given a comprehensive nursing using stoma powder, skin protective film, hydrocolloid dressing and one-piece ostomy pouch. The IAD skin healing condition, healing time, time-consuming and frequency of nursing were observed and compared between the two groups. Results The skin healing time of patients in the observation group was significantly lower than that of the control group (3. 27±1. 02 d vs. 5. 41±1. 93 d, P<0. 05), and the healing effect in the observation group was significantly higher than that in the control group (P<0. 05). Less time-consuming and lower frequency of nursing were found in the observation group compared with those in the control group(P＜0. 05). Conclusion The combination use of ostomy powder, skin protective film, hydrocolloidal dressing and one-piece ostomy pouch can effectively improve the perianal skin healing, shorten the time-consuming of skin care and improve the quality of nursing among ICU patients with IAD. (目的 探讨护肤粉、皮肤保护膜、水胶体敷料联合一体式造口袋在失禁性皮炎(IAD)患者中的应用效果。方法 选取2019年1月—2020年8月ICU收治的40例重症并发IAD的患者为研究对象为研究对象, 随机分为对照组和观察组, 各20例。对照组患者给予常规护理, 观察组患者给予造口粉、皮肤保护膜、水胶体敷料联合一体式造口袋联合护理。观察2组患者IAD治愈有效率以及皮损愈合时间, 比较2组护理用时和护理次数。结果 观察组IAD疗效优于对照组, 差异有统计学意义(P＜0. 05)。观察组皮损愈合时间(3. 27±1. 02)d, 短于对照组皮损愈合时间(5. 41±1. 93)d, 2组比较差异有统计学意义(P＜0. 05)。观察组护理用时以及护理次数均少于对照组, 差异有统计学意义(P＜0. 05)。结论 将造口粉、皮肤保护膜、水胶体敷料联合一体式造口袋应用于IAD患者中, 可有效促进患者肛周皮肤愈合, 减少重复护理次数, 提高护理质量。)